Smart learning using artificial intelligence: Ways to improve the process of teaching general education subjects in higher education (China's experience) - Wang, Xiaoyu; Li, Yan; Yan, Jing (Russian Journal of Education and Psychology, 2025)
Background. The new wave of revolution in the field of information technology has posed many new challenges to higher education. In the context of the collision of traditional concepts of learning and modern technologies “artificial intelligence + learning”, a new model of smart learning has emerged. At the same time, the integration of artificial intelligence technologies into teaching has given rise to certain problems, the solution of which is urgent, and the main factor that helps to solve them is the formation of a quality level of teaching in the conditions of using SMART-technologies. Purpose. This study aims to identify ways and means to optimize teaching methods in China's higher education institutions in the transition to intelligent teaching with the application of artificial intelligence. The objectives are: to analyze the current problems in the implementation of intelligent teaching with the use of artificial intelligence in universities; to identify on the basis of comparison of empirical and theoretical data the optimal ways of building intelligent teaching (on the example of teaching general education subjects at Heihe University); to present the direction of concrete steps to solve the problems arising in universities Materials and methods. The materials were scientific publications of Russian and Chinese specialists of recent years, as well as empirical data collected by the author at Heihe University). The process of teaching general education subjects was chosen for analysis because of their focus on the formation of the general development of students, the ability to be in society, and the foundation for mastering specialized subjects. The following methods were applied: general theoretical analysis of scientific literature in order to identify the degree of study of the issue; empirical methods of material collection, which formed the basis for analyzing the process of smart learning, and finally the method of system analysis was applied for the final conclusions. Results. In the context of the application of artificial intelligence, in terms of teaching environment, teaching model, teaching staff formation and evaluation mechanism, the practical strategies of intelligent teaching of general education subjects in higher education institutions, which are designed to make teaching more targeted, student learning more personalized, and management methods in higher education institutions more scientific, are discussed by analyzing the teaching process of general education subjects at Heihe University. The article emphasizes the importance for the teacher not only to objectively approach the assessment of learning outcomes, but also to analyze the emerging problems in order to solve them in practice. Practical recommendations for transforming the teaching process during the transition from traditional to smart learning are given, which, in the author's opinion, can optimize the teaching process as a whole, applicable to all disciplines. EDN: EQTHBG